Antitumor and Anti-HIV Agents from Natural Products (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Cancer is the second leading cause of death worldwide, and was accountable for an estimated 9.6 million deaths in 2018. Nowadays, about 1 in 6 deaths in the world is due to cancer. Another major global public health issue is HIV. Over 70 million people have been infected with the HIV virus and about 35 million people have died of HIV-related illness, since the start of the epidemic. We have been fighting against these two serious diseases by finding successful treatments. The discovery of effective drugs is important for fighting cancer and HIV. Natural products, which are secondary metabolites produced by various living organisms, have been playing a principal role in drug discovery and developments, because of their structural and biological diversity. Many clinically used drugs have come from natural products; for example, more than 60% of anticancer drugs currently in clinical use are derived from natural sources. This Special Issue aims to collect original research and review articles focusing on notable and recent contributions to the discovery and development of novel anticancer and anti-HIV drug candidates from natural sources. Up-to-date knowledge from various research fields is welcome. This could be of great interest for scientists working in different research areas, such as natural product chemistry, including isolation and structural elucidation; phytochemistry; medicinal chemistry, including chemically modified natural compounds with improved biological activity; pharmacology; molecular biology; mechanisms of action study using natural products or related compounds; pharmacognosy, etc. Biological studies of natural extracts without an appropriate chemical characterization may not be considered.